(untitled) (American Journal of Islam and Society, 2014)
Educating Muslim Women is a unique study of Muslim women told through the story of Nana Asma’u, a nineteenth-century Fulani woman from Northern Nigeria who became a renowned scholar and greatly impacted Muslim women in Nigeria and beyond. Drawing on history, literary analysis, and ethnography, the volume’s slimness belies a wealth of material that will interest historians, applied linguists, and even sociologists of contemporary Muslim communities. The book’s main argument is that Muslim women have played a greater role in their communities than has previously been understood by historians. While using Nana Asma’u as an example, Boyd and Mack argue that she was not unique and offer painstaking details to show that her society supported and encouraged female Islamic scholarship. In addition, they relate how contemporary women continue to follow her example. The book is organized roughly chronologically, although the chapter titles suggest a thematic organization that is not always adhered to. The introduction offers some background on Sufism, which in later chapters the authors narrow down to the Qadiriyyah order. They define Sufism as “the prayerful pursuit of knowledge aiming to move an individual closer to God” (p. 15). Their focus on knowledge allows them to emphasize Islamic scholarship and education: “Education, like Islam itself, was integral to all parts of daily life” (p. 21). Nineteenth-century schools are depicted as places where pupils learned Qur’anic recitation and received religious blessings, as well as practiced farming, obtained medical treatment, and sought personal advice. By depicting education as central to Islam and Islam as central to Northern Nigerian society, their subsequent account of how involved women ...